Genome Analysis Reveals a Synergistic Mechanism of Ursodeoxycholic Acid and Jasminoidin in Mice Brain Repair After Ischemia/Reperfusion: Crosstalk Among Muti-Pathways - Zhang, Yingying; Li, Haixia; Guo, Huan; Li, Bing; Zhao, Zide; Wang, Pengqian; Wu, Hongli; Liu, Jun; Chen, Yinying; Zhang, Xiaoxu; Wu, Ping; Wang, Zhong; et al. (Frontiers in Pharmacology, 2019)
Studies have shown that combination drug therapy which corresponding treatment involves multiple genes and targets is more effective against cerebral ischemia.To identify the synergistic mechanism of ursodeoxycholic acid and jasminoidin based on differential pathway network , which protect against brain ischemia/reperfusion.A total of 115 mice with focal cerebral ischemia/reperfusion injury were divided into 5 groups: Sham, Vehicle, ursodeoxycholic acid (UA), jasminoidin (JA) and JA and UA combination group (JU). The differentially expressed genes identified by microarray arrays which consisted of 11644 cDNAs were loaded to the GeneGo MetacoreTM software to analyze the enriched pathways and processes among different groups.Among the top ten pathways and processes network，5, 6, and 3 overlapping pathways as well as 5, 3, and 4 overlapping processes network were observed between UA and JA, UA and JU, and JA and JU, respectively. Of which, 3 pathways and 3 process networks were shared across the three groups. Interestingly, 4 representative pathways and 6 process networks were only occured in the JU group. GO process analysis showed 2 processes were shared by all three treatment groups in the top ten process.The UA and JA combination resulted in synergistic effects through affecting muti-signal transduction pathways ,different locations in the same pathway and the new signaling pathway emergenced in drug combination group, those together may enhance the treatment of cerebral ischemia-reperfusion injury through promoting neural cell apoptosis，decreases calcium levels，inhibiting inflammation and protecting neurons.